Does facet tropism negatively affect the response to transforaminal epidural steroid injections? A prospective clinical study - GÜNDÜZ, OSMAN HAKAN; ŞENCAN, SAVAŞ (SPRINGER, 2019)
ObjectiveTo examine the impact of the presence of facet tropism on the results of transforaminal epidural steroid injection for unilateral radicular pain induced by lumbar disc herniation.Materials and MethodsWe included 112 patients diagnosed with unilateral, single-level lumbar disc herniation-induced radicular pain. Injection was planned at relevant levels. The patients were assessed using the Numerical Rating Scale, the Modified Oswestry Disability Index, and the Beck Depression Inventory before the injection and at hour 1, week 3, and month 3 after the injection. Presence of facet tropism was assessed by measuring the facet angles in the L3-4, L4-5, and L5-S1 segments of lumbar MRI T2 sequence axial section.ResultsA significant decrease in the Numerical Rating Scale and an increase in the Modified Oswestry Disability Index scores were detected at all follow-ups in groups comprising 39 patients with and 61 without facet tropism (p<0.05). On comparison, improvement in clinical parameters at week 3 and month 3 in the group without facet tropism was greater (p<0.05). As treatment success is considered to be a 50% reduction in the Numerical Rating Scale scores, 55.2% of the patients attained treatment success at month 3. Further, although the treatment success rate in the group with facet tropism was 34.2%, it was 69% in that without facet tropism (p<0.05).ConclusionFacet tropism correlates with less success of transforaminal epidural steroid injection; therefore, facet tropism may be a worthwhile measurement in a discussion with patients of the benefits of the procedure.
Keywords: Lumbar radicular pain; Transforaminal epidural steroid injection; Facet tropism; LUMBAR DISC HERNIATION; INTERVERTEBRAL DISC; EFFICACY; ORIENTATION; SAFETY; JOINTS; SPINE; RISK; PAIN